Secreted Left Atrial P-Selectin in Mitral Stenosis after PBMV: When to Measure - M. Saifur Rohman (The Indonesian Heart Association, 2014)
The glycoprotein P-selectin, a membrane component of cell storage granules, is rapidly translocated from ?-granules of platelets and the Weibel- Palade bodies of endothelial cells to the cell surface following an inflammatory process or other stimulations. P-selectin is a cell adhesion molecule of activated platelets and endothelial cells of interest because of its role in modulating interactions between blood cells and the endothelium, and also because of the possible use of its soluble form in plasma as a predictor of adverse cardiovascular events.1In endothelial cells, within minutes of its stimulation in vitro by inflammatory mediators, such as histamine, thrombin, or phorbol esters, or hypoxia, Weibel–Palade bodies are mobilized and their von Willebrand factor are degranulated. At the same time, P-selectin is also expressed at the surface as quick astwo minutes after stimulation. However, this expressionis short-lived, reaching its peak after only 10 minutes, declining back to baseline levels after 3 hours. Additional synthesis of P-selectin is brought about within 2 hours by cytokines, such as interleukin-1 (IL-1), tumor necrosis factor-? (TNF-?), and by thrombin, lipopolysaccharide or oxygen radicals. Immunofluorescence and confocal laser cytometry are usually used to measure the translocation upon this activation.1